Network-assisted diversity for random access wireless networks - Tsatsanis, M.K.; Ruifeng Zhang; Banerjee, S. (IEEE transactions on signal processing, 2000)
A novel viewpoint to the collision resolution problem is introduced for wireless slotted random access networks. This viewpoint is based on signal separation principles borrowed from signal processing problems. The received collided packets are not discarded in this approach but are exploited to extract each individual user packet information. In particular, if k users collide in a given time slot, they repeat their transmission for a total of k times so that k copies of the collided packets are received. Then, the receiver has to resolve a k/spl times/k source mixing problem and separate each individual user. The proposed method does not introduce throughput penalties since it requires only k slots to transmit k colliding packets. Performance issues that are related to the implementation of the collision detection algorithm are studied. The protocol's parameters are optimized to maximize the system throughput.